Maternal health care services utilization and associated factors among women in Zoba Maekel, Eritrea 2022: a community based study - Ghirmai, Lidia; Ghirmay Ghebreigziabher; Suleman Mohammed Osman; Tesfay Sahle Embaye; Weldeab Gebresilasie Debesay; Zerom Asmerom Gebregergis; Eyasu H. Tesfamariam (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Introduction: Studies reveal that regular utilization of maternal health care services reduces maternal morbidity and mortality in which these services are affected by complex factors which may be similar across populations. Methods: A community based cross sectional study was conducted from February to May of 2022. A total of 607 women who gave birth in the last 2 years and residing in the area for at least 6 months were selected by two stage cluster sampling technique. A predesigned and pretested questionnaire was used to collect data via face to face interview technique. Chi-square test and multivariable logistic regression were used for data analysis using SPSS (Version 26). Results: Magnitude of maternal health care services utilization was found as; attending antenatal care 99.9%, institutional delivery 99.3% and postnatal care 91.4%. The majority (91.4%) were aware of postnatal care. The proportion (91.5%) of women who utilized postnatal care among those with awareness about it was significantly greater (p<0.001) than the proportion of women who utilized it and with no awareness (63.5%). The nationwide lockdown due to COVID- 19, sudden onset of labor, feeling well were barriers to attending antenatal care, institutional delivery and postnatal care services respectively. Conclusion: Prevalence of antenatal care, institutional delivery and postnatal care services was higher than the national estimate. Improving the quality of care around the time of pregnancy, birth and postpartum is recommended to continuously sensitize the community about the services and further increase the utilization.